Spend time outdoors for your brain – an in-depth longitudinal MRI study. (16th March 2022) - Kühn, Simone; Mascherek, Anna; Filevich, Elisa; Lisofsky, Nina; Becker, Maxi; Butler, Oisin; Lochstet, Martyna; Mårtensson, Johan; Wenger, Elisabeth; Lindenberger, Ulman; Gallinat, Jürgen
Abstract: Objectives: The effects of nature on physical and mental health are an emerging topic in empirical research with increasing influence on practical health recommendations. Here we set out to investigate the association between spending time outdoors and brain structural plasticity in conjunctions with self-reported affect. Methods: We established the Day2day study, which includes an unprecedented in-depth assessment of variability of brain structure in a serial sequence of 40–50 structural magnetic resonance imaging (MRI) acquisitions of each of six young healthy participants for 6–8 months ( n = 281 MRI scans in total). Results: A whole-brain analysis revealed that time spent outdoors was positively associated with grey matter volume in the right dorsolateral prefrontal cortex and positive affect, also after controlling for physical activity, fluid intake, free time, and hours of sunshine. Conclusions: Results indicate remarkable and potentially behaviorally relevant plasticity of cerebral structure within a short time frame driven by the daily time spent outdoors. This is compatible with anecdotal evidence of the health and mood-promoting effects of going for a walk. The study may provide the first evidence for underlying cerebral mechanisms of so-called green prescriptions with possible consequences for future interventions in mental disorders.